We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
135
1
avatar

Help please!!!

Find all solutions x to the equation, \((x^4 -11x^3+24x^2) - (4x^2 - 44x + 96) = 0\)

 Sep 24, 2018
 #1
avatar+5224 
+1

\(x^4-11x^3+24x^2=x^2(x^2-11x+24) \\ (4x^2-44x+96) = 4(x^2-11x+24) \\ x^4-11x^3+24x^2 - (4x^2-44x+96) =(x^2-11x+24)(x^2-4) = \\ (x-8)(x-3)(x-2)(x+2) \\ \text{and thus the solutions are }\\ x=8,~3,~2,~-2\)

.
 Sep 24, 2018

4 Online Users

avatar